2011
DOI: 10.1007/s00468-011-0590-6
|View full text |Cite
|
Sign up to set email alerts
|

Age and radial growth pattern of four tree species in a subtropical forest of China

Abstract: Subtropical forests are usually composed of many tree species. Knowledge of the age and radial growth variation of the dominant tree species is useful for understanding forest dynamics and community structure and function. The aims of this study are to explore whether there are identifiable annual growth rings in the main tree species and to examine the growth characteristics within and among the species in Mount Gutian subtropical forest of China. The results showed that four out of eight tree species from wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 35 publications
1
14
0
Order By: Relevance
“…Tree-ring samples of O. ferruginea showed clearly visible and cross-datable rings, depending on the condition of the tree and location, because trees located on steep slopes with rugged topography have tree-rings with irregular pattern and difficult to distinguish or to cross-date ( Figure 6A and 6B). Similar trends have been reported by White (2007) in Oak, Arnan et al (2012) in Olea europaea and Xing et al (2012) in other broad leaved species. Therefore, a number of forests need to be explored with a large number of samples at different altitudes, slope angles and exposure for better understanding of the growth behavior of the particular species.…”
Section: Age Structure and Ring Characteristicssupporting
confidence: 89%
See 2 more Smart Citations
“…Tree-ring samples of O. ferruginea showed clearly visible and cross-datable rings, depending on the condition of the tree and location, because trees located on steep slopes with rugged topography have tree-rings with irregular pattern and difficult to distinguish or to cross-date ( Figure 6A and 6B). Similar trends have been reported by White (2007) in Oak, Arnan et al (2012) in Olea europaea and Xing et al (2012) in other broad leaved species. Therefore, a number of forests need to be explored with a large number of samples at different altitudes, slope angles and exposure for better understanding of the growth behavior of the particular species.…”
Section: Age Structure and Ring Characteristicssupporting
confidence: 89%
“…The wood samples were allowed to be air-dried, glued in wood skeleton; tracheid's were vertically aligned and sanded with a progressively fine sand paper until a fine polished surface was obtained (Speer 2010). Age was determined by counting total number of rings from the outer most rings to the pith with extrapolation for any missing portion of the total radius (Brienen and Zuidema 2006;Xing et al 2012). Age was determined by counting total number of rings from the outer most rings to the pith with extrapolation for any missing portion of the total radius (Brienen and Zuidema 2006;Xing et al 2012).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For three of the four species Lang et al (2012a) found species-specific differences in sapling growth in the same study region. Furthermore, Chen et al (1999) observed high growth rates for saplings of S. superba in forest gaps, and Q. serrata was recorded to be very slow growing (Xing et al 2012). However, further studies are needed to elucidate the relationships between functional traits and growth rates in these subtropical forests.…”
Section: Discussionmentioning
confidence: 99%
“…This can be attributed to the varying eco-physiological characteristics of the tree species coexisting in a given forest ecosystem [6]. It is, therefore, valuable to have knowledge on age and radial growth patterns of dominant tree species across their lifespans to understand forest dynamics and facilitate sustainable forest management [7][8][9]. Besides, information on the occurrence and frequency of periods of releases and suppressions is vital to understand differences in life histories among species [10,11].…”
Section: Introductionmentioning
confidence: 99%